PREDICTION ANALYSIS OF FOULING MODEL ON HEAT EXCHANGER IN THE CRUDE OIL REFINERY - Hairul Huda; Renanto Renanto; Totok Ruki Biyanto; Rif'an Fathoni; Tantra Diwa Larasati (Jurnal Chemurgy, 2022)
Fouling mainly occurs in the oil industry. Fouling is an unwanted deposit in HE (heat exchanger). Reliable fouling models are scarce, although empirical and theoretical models have been proposed to describe fouling in heat exchangers. The general models of empirical fouling used are linear, falling rate, and asymptotic. The research methodology begins with the acquisition and use of operational fouling data, which is then followed by the use of an asymptotic fouling model and ends with calculating the thickness of fouling in all HE. The object of this research study is all HE in the crude oil refinery HEN (heat exchanger network). The aim of this research is to use the asymptotic fouling model and get the fouling thickness. The fouling resistance from time to time increases, but in the end, it tends to be stationary, where for the final value, the highest fouling resistance is in HE-10, namely 14.8E-03 (m2°C/W), and the lowest value is fouling resistance at HE- 01 is 1.27E-03 (m2°C/W). The thickness of HE fouling in asymptotic conditions indicates that HE undergoes the same deposition process as suppression.Keywords: fouling, heat exchanger, asymptotic, crude oil refinery, heat exchanger network